A methyltransferase‐like 14/miR‐99a‐5p/tribble 2 positive feedback circuit promotes cancer stem cell persistence and radioresistance via histone deacetylase 2‐mediated epigenetic modulation in esophageal squamous cell carcinoma - Zhenchuan Liu (Wiley, 2021)
Abstract Background Esophageal squamous cell carcinoma (ESCC) is a highly aggressive and treatment‐resistant tumor. The biological implications and molecular mechanism of cancer stem‐like cells (CSCs) in ESCC, which contribute to therapeutic resistance such as radioresistance, remain elusive. Methods Quantitative real‐time polymerase chain reaction, western blotting, immunohistochemistry, and in situ hybridization assays were used to detect methyltransferase‐like 14 miR‐99a‐5p tribble 2 (METTL14/miR‐99a‐5p/TRIB2) expression in ESCC. The biological functions of METTL14/miR‐99a‐5p/TRIB2 were demonstrated in vitro and in vivo. Mass spectrum analysis was used to identify the downstream proteins regulated by TRIB2. Chromatin immunoprecipitation (IP), IP, N6‐methyladenosine (m6A)‐RNA IP, luciferase reporter, and ubiquitination assays were employed to explore the molecular mechanisms underlying this feedback circuit and its downstream pathways. Results We found that miR‐99a‐5p was significantly decreased in ESCC. miR‐99a‐5p inhibited CSCs persistence and the radioresistance of ESCC cells, and miR‐99a‐5p downregulation predicted an unfavorable prognosis of ESCC patients. Mechanically, we unveiled a METTL14‐miR‐99a‐5p‐TRIB2 positive feedback loop that enhances CSC properties and radioresistance of ESCC cells. METTL14, an m6A RNA methyltransferase downregulated in ESCC, suppresses TRIB2 expression via miR‐99a‐5p‐mediated degradation of TRIB2 mRNA by targeting its 3′ untranslated region, whereas TRIB2 induces ubiquitin‐mediated proteasomal degradation of METTL14 in a COP1‐dependent manner. METTL14 upregulates miR‐99a‐5p by modulating m6A‐mediated, DiGeorge critical region 8‐dependent pri‐mir‐99a processing. Hyperactivation of TRIB2 resulting from this positive circuit was closely correlated with radioresistance and CSC characteristics. Furthermore, TRIB2 activates HDAC2 and subsequently induces p21 epigenetic repression through Akt/mTOR/S6K1 signaling pathway activation. Pharmacologic inhibition of HDAC2 effectively attenuates the TRIB2‐mediated effect both in vitro and in patient‐derived xenograft models. Conclusion Our data highlight the presence of the METTL14/miR‐99a‐5p/TRIB2 axis and show that it is positively associated with CSC characteristics and radioresistance of ESCC, suggesting potential therapeutic targets for ESCC treatment.